Molecular Biocompatibility of a Silver Nanoparticle Complex with Graphene Oxide to Human Skin in a 3D Epidermis In Vitro Model - Marlena Zielińska-Górska; Ewa Sawosz; Malwina Sosnowska; Anna Hotowy; Marta Grodzik; Konrad Górski; Barbara Strojny-Cieślak; Mateusz Wierzbicki; André Chwalibog (MDPI AG, 2022)
Silver nanoparticles (AgNP) can migrate to tissues and cells of the body, as well as to agglomerate, which reduces the effectiveness of their use for the antimicrobial protection of the skin. Graphene oxide (GO), with a super-thin flake structure, can be a carrier of AgNP that stabilizes their movement without inhibiting their antibacterial properties. Considering that the human skin is often the first contact with antimicrobial agent, the aim of the study was to assess whether the application of the complex of AgNP and GO is biocompatible with the skin model in in vitro studies. The conducted tests were performed in accordance with the criteria set in OECD TG439. AgNP-GO complex did not influence the genotoxicity and metabolism of the tissue. Furthermore, the complex reduced the pro-inflammatory properties of AgNP by reducing expression of IP-10 (interferon gamma-induced protein 10), IL-3 (interleukin 3), and IL-4 (interleukin 4) as well as MIP1β (macrophage inflammatory protein 1β) expressed in the GO group. Moreover, it showed a positive effect on the micro- and ultra-structure of the skin model. In conclusion, the synergistic effect of AgNP and GO as a complex can activate the process of epidermis renewal, which makes it suitable for use as a material for skin contact.